A Cross-sectional Study of the Relationship between Age, Body Mass, Pain, and Walking Limitations in Women with Knee Osteoarthritis - Marks, R. (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Knee osteoarthritis (OA) causes significant physical disability in many people. While some research indicates that women with this disease suffer more than men, few studies have attempted to describe the severity and effect of this disease specifically among women with moderate knee osteoarthritis, as well as the relationships that exist between their perceived health status and well-known physical, emotional, and perceptual factors found in this disease. This exploratory research aimed to better understand the factors that influence how the condition is viewed, as well as to explain the level of pain and function in women with mild to moderate knee osteoarthritis and how this affects the condition. The records of 20 women with the disease who had undergone several tests using standardised procedures and approved instruments were reviewed. The primary outcome measure was the perceived impact of the disease using the Arthritis Impact Measurement Scale. Six-minute walking time, fastest walking velocity, self-reported discomfort, pain and functional self-efficacy, body mass index, and depression were all used as secondary outcome indicators. T-tests and correlational studies were conducted on the variables. Results demonstrated pain is the clinical factor most consistently impacting the disease experience, along with deficiencies in walking ability (p <0.05). Important mediating variables of ambulatory capacity were body mass and pain self-efficacy.